PERLINDUNGAN HKI BAGI PRODUK USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI TENGAH DIGITALISASI EKONOMI - Annisa Islami; Salma Yusriyyah; Widia Nur Fatwa; Astri Maisarah Fadhilah (SINERGI : Jurnal Riset Ilmiah, 2026)
Intellectual Property Rights (IPR) protection for Micro, Small and Medium Enterprises (MSMEs) products in the context of rapid economic digitization in Indonesia. The main focus of the research is to identify the level of understanding and awareness of MSMEs of IPR, the obstacles faced in registering and managing IPR, and the role of the government and related institutions in facilitating such protection through digitization of services and education. The research method used is a qualitative study with data analysis from primary and secondary sources, including government policies and interviews with MSME actors. The results show that despite increased awareness, MSMEs still face cost constraints, complicated procedures, and limited access to information. Digitalization of IPR services and education programs are key to overcoming these obstacles, while supporting MSMEs in expanding market access and product competitiveness. The findings recommend simplifying the IPR registration process, strengthening IPR literacy, and increasing policy incentives as strategic efforts to strengthen IPR protection for MSMEs in the digital era. This research is expected to contribute to the development of more effective IPR protection policies and practices for Indonesia's creative economy.